STUDENTS’ NONVERBAL COMMUNICATION IN INSTAGRAM POST AT TENTH GRADE OF SMA NEGERI 1 CILEGON (2020) - FIA ADRIANI; NURHAEDA GAILEA; Delsa Miranty (Jurnal Bebasan, 2020)
The objective of this research is to investigate the use of nonverbal communication by students of SMA Negeri 1 Kota Cilegon in Instagram post. The researcher used qualitative method witha case study as a research design. The participants of this research were the English teacher and the students of X IPS 1 at SMA Negeri 1 Cilegon. The students were asked to post their performance in Instagram. The researcher used observation to find out the types of nonverbal communication that mostly used by the students in their Instagram post. Meanwhile, questionnaires and interview were used to describe the English teacher’s and students’ responses on the use of nonverbal communication. The data analysis showed that the most occurred nonverbal communication was gesture. The English teacher and students also gave a positive response to the use of nonverbal communication in the students’ performance.